Correlation Peer Support with Body Image (Self-Image) of Adolescent at SMP Pelita 1 Depok - Elpinah Widiastuti; Diah Ratnawati (Universitas Muhammadiyah Tangerang, 2020)
This research is more purpose know the relationship of peer support with body image on adolescent SMP Pelita 1 Depok. The method used with the quantitative approach make us of cross sectional (potong litang) with increase the sampel of 100 respondent at SMP Pelita 1 Depok with startified sampling technique. Method of data analysis will do it by using chis square test. Result of data analysis was obtained result p=0,001. This is show that there is a relationship peer support with body image on adolescent SMP Pelita 1 Depok at significant level 0,005, also obtained the value OR=4,173 means that responden who have negative peer support have a 4 kali change to have a negative body image in comparison with respondents who have positive peer support. From the result of this research expected to give a positive to be behavior, and of individual throughts and feelings for friends will give supports for their body image, so adolescent more confident again their body image.Keywords: Adolescent, Body Image, Peer Support